Seasonal Occurrence, Horizontal Movements, and Habitat Use Patterns of Whale Sharks (Rhincodon typus) in the Gulf of Mexico - Hoffmayer, Eric R.; McKinney, Jennifer A.; Franks, James S.; Hendon, Jill M.; Driggers, William B.; Falterman, Brett J.; Galuardi, Benjamin; Byrne, Michael E. (Frontiers in Marine Science, 2021)
In the northern Gulf of Mexico (GOM), whale sharks (Rhincodon typus) form large aggregations at continental shelf-edge banks during summer; however, knowledge of movements once they leave aggregation sites is limited. Here we report on the seasonal occurrence of whale sharks in the northern GOM based on over 800 whale shark sightings from 1989 to 2016, as well as the movements of 42 whale sharks tagged with satellite-linked and popup satellite archival transmitting tags from 2008 to 2015. Sightings data were most concentrated during summer and fall often with aggregations of individuals reported along the continental shelf break. Most sharks (66%) were tagged during this time at Ewing Bank, a known aggregation site off the coast of Louisiana. Whale shark track duration ranged from three to 366 days and all tagged individuals, which ranged from 4.5 to 12.0 m in total length, remained within the GOM. Sightings data revealed that whale sharks occurred primarily continental shelf and shelf-edge waters (81%) whereas tag data revealed the sharks primarily inhabit continental slope and open ocean waters (91%) of the GOM. Much of their time spent in open ocean waters was associated with the edge of the Loop Current and associated mesoscale eddies. During cooler months, there was a net movement southward, corresponding with the time of reduced sighting reports. Several sharks migrated to the southwest GOM during fall and winter, suggesting this region could be important overwintering habitat and possibly represents another seasonal aggregation site in this region. The three long-term tracked whale sharks exhibited interannual residency, returning to the vicinity where they were originally tagged one year later. The broad-scale GOM-wide movements observed in this study demonstrate multi-national, cooperative efforts are needed to improve management of whale sharks in the region.